London in 1731 - Gonzales, Manoel, Don; Defoe, Daniel, 1661?-1731 (Salt Lake City, UT : Project Gutenberg, 2001)
"London in 1731" by Don Manoel Gonzales is a historical account likely written in the late 19th century. The book provides a detailed examination of London during the early 18th century, exploring its architecture, society, government, and commerce. Gonzales, possibly reflecting the perspective of a well-traveled merchant, portrays the city and its various social strata through careful observation and narrative. The opening of "London in 1731" introduces readers to the extensive geography of the city, describing its layout and the significance of various districts and landmarks. The text meticulously details the dimensions of London, the prominent gates such as Aldgate and Bishopsgate, and key features like the Tower of London and its storied history. Right from the start, Gonzales establishes a comprehensive framework for understanding the structure of the city by cataloging its ward divisions, marketplaces, and civic buildings. Overall, this opening sets the stage for a rich exploration of London$1 (Bs urban life and its evolving character in the context of the 18th century. (This is an automatically generated summary.)s
Attributed to Defoe.
Release date is 2001-09-01
Transcribed from the 1888 Cassell & Co. edition by David Price
Keywords: London (England) -- History -- 18th century; London (England) -- Description and travel